Oral disease burden of dentate older adults living in long-term care facilities: FINORAL study - Lina Julkunen; Kaija Hiltunen; Hannu Kautiainen; Riitta K. T. Saarela; Kaisu H. Pitkälä; Päivi Mäntylä (BMC, 2021)
Abstract Background A growing number of older adults have natural teeth and are at high risk of oral diseases, which are induced by oral bacterial accumulation and proceed unnoticed and quietly. Our aim was (1) to examine the association of oral disease burden (ODB) with health and functioning among dentate long-term care residents, and (2) to find easily detectable signs for nurses to identify residents' poor oral health. Methods In this cross-sectional observational study dentists examined 209 residents' oral status, and nurses assessed residents for their functioning and nutrition in long-term care facilities in Helsinki, Finland. ODB was defined by asymptotic dental score (ADS). Six clinical signs of residents' poor oral health were considered as potentially easy for nurses to detect: lesions on lips, teeth with increased mobility, lesions on oral mucosa, eating soft or pureed food, unclear speech, and needing assistance in eating. The association of these was tested with high ODB as outcome. Results Participants were grouped according to their ADS scores: low (n = 39), moderate (n = 96) and high ODB (n = 74). ODB was linearly associated with coronary artery disease and poor cognitive and physical functioning: needing assistance in eating, poor ability to make contact, and unclear speech but not with other diseases including dementia or demographic characteristics. Furthermore, ODB was linearly associated with eating soft or pureed food. Of the six selected, easily detectable signs, having at least two positive signs gave 89% sensitivity to detecting high ODB. Conclusion Poor oral health was common and ODB accumulated among residents with poor functioning. Nurses may use a few easily detectable signs to screen residents' oral health when considering a resident's need for consultation with an oral health professional.